THE DEVELOPMENT OF STUDENT WORKSHEET BASED CONTEXTUAL INQUIRY OF AQUATIC MICROBIOLOGY MATERIAL IN STUDENTS DEPARTMENT OF BIOLOGY EDUCATION - Yusnita Anwar Nasution; Hasruddin Hasruddin; Tumiur Gultom (EDUSAINS, 2018)
PENGEMBANGAN LEMBAR KERJA MAHASISWA (LKM) BERBASIS INKUIRI KONTEKSTUAL MATERI MIKROBIOLOGI AIR PADA MAHASISWA PENDIDIKAN BIOLOGI AbstractThe study aims to determine: (1) The results expert material validation of worksheet that has been developed; (2) The results of design experts validation of worksheet that has been developed; (3) Response of lecturer of microbiology subject to worksheet that has been developed; (4) Perception of University of Medan Biology Education students to Worksheet that has been developed; (5) The eligibility of Worksheet for Biology Education students of State University of Medan. This development study uses a modified Borg & Gall model as needed to produce a product of a contextual inquiry-based worksheet. The results of material expert validation to microfinance based worksheet in context of water microbiology materials that have been developed with the feasibility of the contents show 93.75% included in the category of very good; Feasibility of presentation shows 91.44% included in the category of very good; The feasibility of the contextual inquiry component indicates 87.82% in the category of good good; The design validation results show that 89.06% percentage is included in the category of very good; The result of the assessment by the lecturer shows 93.75% is included in the category of very good; Individual tests show  86,66% included in the category of very good; Small group test showed 87.22% included in the category of very good; The test of the restricted group shows 91.12% included in the the category  of very good. Test based on the data the product worksheet based on inquiry of contextual material of water microbiology which have been developed feasible to be used for student as worksheet in Microbiology course.AbstrakPenelitian ini bertujuan untuk mengetahui: (1) Hasil validasi ahli bahan lembar kerja yang telah dikembangkan; (2) Hasil validasi ahli desain lembar kerja yang telah dikembangkan; (3) Tanggapan dosen mata kuliah mikrobiologi terhadap lembar kerja yang telah dikembangkan; (4) Persepsi mahasiswa Pendidikan Biologi Universitas Medan terhadap Lembar Kerja yang telah dikembangkan; (5) Kelayakan Lembar Kerja untuk mahasiswa Pendidikan Biologi Universitas Negeri Medan. Studi pengembangan ini menggunakan model Borg & Gall yang dimodifikasi sesuai kebutuhan untuk menghasilkan produk dari lembar kerja berbasis inkuiri kontekstual. Hasil validasi ahli materi terhadap LKM berbasis microfinance dalam konteks bahan mikrobiologi air yang telah dikembangkan dengan kelayakan isinya menunjukkan 93,75% termasuk dalam kategori sangat baik; Kelayakan presentasi menunjukkan 91,44% termasuk dalam kategori sangat baik; Kelayakan komponen penyelidikan kontekstual menunjukkan 87,82% dalam kategori barang bagus; Hasil validasi desain menunjukkan bahwa 89,06% termasuk dalam kategori sangat baik; Hasil penilaian oleh dosen menunjukkan 93,75% termasuk dalam kategori sangat baik; Tes individu menunjukkan 86,66% termasuk dalam kategori sangat baik; Uji kelompok kecil menunjukkan 87,22% termasuk dalam kategori sangat baik; Tes kelompok terbatas menunjukkan 91,12% termasuk dalam kategori sangat baik. Uji berdasarkan data lembar kerja produk berdasarkan permintaan bahan kontekstual mikrobiologi air yang telah dikembangkan layak untuk digunakan untuk siswa sebagai lembar kerja di Mikrobiologi saja.